How Does Philippines's Education System Compared to Finland's? - Osias Kit T. Kilag; Junrel P. Zarco; Maribel B. Zamora; Jelly D. Caballero; Claudine Acece L. Yntig; Jodhel D. Suba-an; John Michael Sasan (Future Science, 2023)
This study examines the differences between the education systems in Finland and the Philippines. The education systems in both countries have significant differences in terms of policies, teacher qualifications, and curriculum structure. Finland has a highly decentralized curriculum that allows teachers to develop their own curriculum according to the needs and interests of students, while the curriculum in the Philippines is centralized and designed by the central government. The quality and competence of teachers in Finland are also higher compared to those in the Philippines, where a Bachelor's or Diploma Four degree is the minimum requirement for teaching. Finland's success in education can be attributed to the government's persistence and consistency in implementing education policies formulated over the years, and their emphasis on teacher quality and competence. On the other hand, the Philippines has struggled to improve the quality of education, with some policies having little to no positive impact. Given the differences between the two education systems, the study suggests that the Philippines should learn from Finland's education system and adopt some of its policies to improve its own education system. By doing so, the Philippines can improve the quality of education and potentially achieve the same success that Finland has achieved.